Assessing the Effectiveness of Turkey’s 2019 Reverse Brain Drain Program in Reducing Skilled Emigration - Kalyshenko, Daria; Pantea, Smaranda; Agustina, Shirley Basauli; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines the effectiveness of Turkey’s Reverse Brain Drain Program (TÜBİTAK 2232-A), launched in 2019 with the aim of reducing the emigration of qualified specialists and strengthening the national potential in the field of research and development (R&D). The study focuses on the relationship between government investment in R&D and the level of researcher employment, with particular attention to the priority sectors covered by the program, including information technology, healthcare, and defense. A mixed-method approach is applied, incorporating inflation-adjusted government expenditures, full-time equivalent (FTE) employment data, and sectoral trends for the period from 2015 to 2023. The study also includes qualitative case studies of returning researchers to assess institutional outcomes and political significance. Thus, the research is aimed at evaluating the effectiveness of the 2232-A program through the comparison of government investment, researcher employment, and sectoral trends, taking into account the macroeconomic situation of the scientific sphere in Turkey.
Vedoucí práce: Smaranda Pantea
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses